Strategi Peningkatan Partisipasi Orang Tua Dalam Pendidikan Anak di Sekolah Dasar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The role of parents in children's education at the elementary level significantly influences learning success and character development. This study aims to analyze the forms of parental participation, identify existing barriers, and formulate strategies to enhance their involvement in children’s education. The research employs a literature study method by reviewing relevant sources such as books, journals, and scientific articles. The results indicate that the level of parental participation in Indonesia remains moderate, with most involvement focused on financial support rather than academic or emotional guidance. Forms of participation include assisting with learning, providing motivation, supervision, and collaboration with schools. Collaborative strategies between schools and parents through effective communication and sustainable partnership programs are essential to improving the quality of elementary education.